Bondholders vs. bond-sellers? Investment banks and conditionality lending in the London market for foreign government debt, 1815-1913 - Marc Flandreau; Juan Flores (European Historical Economics Society (EHES), 2011)
This paper offers a theory of conditionality lending in 19th-century international capital markets. We argue that ownership of reputation signals by prestigious banks rendered them able and willing to monitor government borrowing. Monitoring was a source of rent, and it led bankers to support countries facing liquidity crises in a manner similar to modern descriptions of "relationship" lending to corporate clients by "parent" banks. Prestigious bankers' ability to implement conditionality loans and monitor countries' financial policies also enabled them to deal with solvency. We find that, compared with prestigious bankers, bondholders' committees had neither the tools nor the prestige required for effectively dealing with defaulters. Hence such committees were far less important than previous research has claimed.
Keywords: N20; F34; 330; Bondholders; Investment banks; certification